Ursula Wingate. The Effectiveness of Different Learner Dictionaries: An Investigation into the Use of Dictionaries for Reading Comprehension by Intermediate Learners of German. - Abecassis, Michaël (Lexikos, 2006)
Unlike the long tradition of EFL dictionaries, German learners’ dictionaries are quite recent and were first marketed in the 1990s. Ursula Wingate’s book is quite unique, since studies in German learners’ dictionaries are very few, as is empirical research conducted in dictionary use.